24‐hour pH‐impedance monitoring on therapy to select patients with refractory reflux symptoms for antireflux surgery. A single center retrospective study. Issue 1 (3rd November 2015) - Desjardin, M.; Luc, G.; Collet, D.; Zerbib, F.
Abstract: Background: Treatment of gastro‐esophageal reflux refractory symptoms is challenging. This monocenter retrospective study assessed the value of preoperative pH‐impedance monitoring 'on' therapy to predict functional outcome after laparoscopic fundoplication in patients with refractory reflux symptoms. Methods: Patients with a preoperative pH‐impedance monitoring 'on' proton pump inhibitors (PPIs) twice daily were assessed at least 6 months after a laparoscopic fundoplication for refractory reflux symptoms. Failure of fundoplication was defined by a Visick score > 2. Postoperative symptoms were assessed by the reflux disease questionnaire (RDQ). The pH‐impedance parameters analyzed were the number of reflux events (total, acid, non‐acid), esophageal acid exposure time, esophageal bolus exposure time, and symptom‐reflux association defined by symptom index (SI) >50% and symptom association probability (SAP) >95%. Key Results: Thirty‐three patients (18 female patients, median age 46 years) were assessed after a mean follow‐up of 41.3 (range 7–102.2) months. Seven (21.2%) patients were considered as failures. Compared to patients with favorable outcome, these patients were more often 'on' PPI therapy (86% vs 23%, p < 0.05) and had higher RDQ scores in each domain: heartburn ( p < 0.05), regurgitation ( p < 0.05) and dyspepsia ( p < 0.05). A positive SAP was the only pH‐impedance parameter statistically associated with successful postoperative outcome ( p = 0.004). Conclusions & Inferences: On therapy, a preoperative positive symptom association probability is the only pH‐impedance parameter associated with favorable outcome after laparoscopic fundoplication for refractory reflux symptoms. These results should be confirmed by prospective studies. Abstract : In patients with refractory reflux symptoms, the role of antireflux surgery is debated. There is no consensus regarding patients' selection for surgery. We conducted a retrospective study in two groups of patients with favorable ( n = 26) and unsatisfactory outcomes ( n = 7) who had preoperative esophageal pH‐impedance monitoring on double dose PPIs. On therapy, neither pH‐impedance reflux parameters nor positive SI could help to discriminate patients with favorable and unsatisfactory outcomes. Only a positive SAP was significantly associated with successful clinical outcome. View the podcast on this paper at the following sites: iTunes:https://itunes.apple.com/dk/podcast/neurogastroenterology-motility/id1065452103 Youtube:https://www.youtube.com/watch?v=pN2J3vjF4dY&feature=em-upload_owner